Educational inequality after high school graduation - there is a way to change that: An inquiry into the effectiveness of an intensive counseling program 1.5 years after high school graduation - Melinda Erdmann; Irena Magdalena Pietrzyk; Juliana Schneider; Marcel Helbig; Marita Jacob; Jutta Allmendinger (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2022)
The German education system is characterized by strong social inequalities in university access. These may be reduced by offering individual counseling sessions to students in their final two years of high school. The study "Zukunftsund Berufspläne nach dem Abitur" (ZuBAb)1 examines how such intensive and individual guidance counseling affects participants' educational trajectories using an experimental design that allows for making internally valid inferences regarding the program's causal effects. Based on data (N = 1,064) collected about 1.5 years after participants earned their university entrance diploma (Abitur), we looked at whether the program promotes university enrollment among persons of low educational origin, whether it reduces educational inequalities at the transition from school to higher education, and how educational trajectories change in the period between 0.5 years and 1.5 years after graduation, depending on whether students received counseling or not. The results show a strong program effect of 8 percentage points on university enrollment rates among persons of low educational origin and a strong inequality-reducing effect of the counseling program (15 percentage points or 71 percent in relative terms). The program's positive impact stems from the fact that participation tends to improve fit between a student's academic performance and the educational pathway chosen after graduation. Moreover, the results show that positive program effects begin to emerge only after 1.5 years post-graduation (whereas no positive effect was found 0.5 years after graduation) because persons who start a gap year experience (e.g., voluntary community service year) right after earning their Abitur are especially likely to benefit from program participation. Additionally, a detailed breakdown of educational trajectories over time shows that the program not only promotes university enrollment among persons of low educational origin and enrollment in vocational training schemes among persons of high educational origin but also, in descriptive terms, helps graduates start any kind of post-school educational pathway. The findings make clear that studies designed to make comprehensive inferences about the effects of educational programs should also consider persons of high educational origin and should look not only at university enrollment but also at the smooth transition to any kind of postsecondary educational pathway. They also show that researchers and practitioners need to be patient because there may be some delay until measurable positive effects of individual counseling sessions begin to unfold.
Keywords: 330; educational inequality; university enrollment; intervention